Experimental study on the operating characteristics of self-circulating evaporative inner cooling system for high power rectifier equipment. (September 2022) - Yan, Jing; Ruan, Lin
Abstract: In the self-circulating evaporative cooling system for high power rectifier equipment, horizontal and vertical hollow copper bars constitute a complex nonlinear system. The operating characteristics of system may be affected by parallel affect. Then in this paper, experiment setup was established for one bridge according 240 kVA thyristor rectifier. Through experiment got the data of pressure and flow rate as the heat load was gradually increased. When the system work under rated condition, the temperature is lower than 80 °C. The system with composite structure shows great difference with simple structure. Then the operating characteristics was researched through a series of experiments. Meanwhile, the flow resistance of the three flow passages was studied according traditional calculation models. The homogeneous model correlation was chosen for No 1 and No 2 flow passage, and Friedel correlation was chosen for No 3 flow passage here. Results shows that the relative error is less than 25%. The work in this paper can provide guidance for optimal design of system and application in future.